A production process for high temperature resistant ultra-fine enameled wire

Through the preparation of modified polyimide paint, the problem of enameled wire being prone to cracking and insufficient adhesion in high-temperature environments is solved, and the excellent high-temperature resistance and adhesion of enameled wire is achieved, ensuring the safe operation and service life of electrical equipment.

CN119108149BActive Publication Date: 2025-04-22ZHEJIANG WEILIFANG COMPOSITE MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411324465.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-04-22
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Ordinary enameled wires are prone to cracking and aging in high-temperature environments, and insufficient adhesion between polyimide paint and metal wires can easily lead to current leakage and safety hazards.

Method used

Modified polyimide paint is used to prepare a modified polyimide paint with excellent adhesion and high temperature resistance by adding 3-amino-5-mercapto-1,2,4-triazole into the reaction of polycarbonate diol and dimethylvinyl chloride silane to form polycarbonate diamine, and combined with functional dianhydride, chain-extended bismaleimide solution, boron nitride and other components to prepare a modified polyimide paint with excellent adhesion and high temperature resistance for the production of enameled wire.

Benefits of technology

It significantly improves the high temperature resistance and adhesion of the enameled wire, prevents current leakage, extends service life, and ensures the safe operation of electrical equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119108149B_ABST
    Figure CN119108149B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of enameled wires, and discloses a production process of a high-temperature resistant ultrafine enameled wire. The enameled wire is prepared by dipping a modified polyimide paint on the surface of a metal conductor, wherein the modified polyimide paint comprises the following raw materials: polycarbonate diamine, N,N-dimethylformamide, functional dianhydride, chain-extended bismaleimide solution, boron nitride, isocyanate, and toluene. The prepared polycarbonate diamine and the functional dianhydride are combined to prepare the modified polyimide paint, so that the modified polyimide paint has excellent adhesion and high-temperature resistance. When the modified polyimide paint is used to prepare the enameled wire, the prepared enameled wire paint film has a strong bonding ability with the metal conductor, can effectively prevent the leakage of current, ensure the safety of the use of electrical equipment, and can still work stably in a long-term high-temperature environment, has good durability, and has a long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of enameled wires, and in particular to a production process for high-temperature resistant ultra-fine enameled wires. Background Art

[0002] Enameled wire is an electromagnetic wire with metal wire as the conductor material and insulating paint coated on the surface. It has good insulation properties and is widely used in motors, electrical appliances, transformers, electronic components and other fields. As a key material, the performance of enameled wire directly affects the operating efficiency and safety of electrical equipment. As a current carrier, enameled wire needs to have good high temperature resistance so that it can maintain stable physical and chemical properties in a complex high temperature environment, prevent aging of the insulation layer, and affect the safety of electrical equipment. At the same time, the enameled wire paint also needs to have excellent bonding effect so that it can be tightly bonded to the metal wire to prevent hollowing, damage or even falling off of the insulation layer, effectively reduce the possibility of current leakage, and ensure the safe operation of electrical equipment.

[0003] However, with the development of industry and the improvement of scientific and technological levels, ordinary enameled wires can no longer meet the use requirements in various environments. Therefore, in actual use, people often improve them. For example, the patent with announcement number CN109135553B discloses a polyimide coil enameled wire for high-speed rail. This polyimide coil enameled wire adds honeycomb silica nanotubes as modified nanomaterials to the polyimide paint. Due to the hollow structure of the nanotubes, it has very good elasticity during contraction and expansion, so it can significantly improve the impact resistance of the polyimide paint layer, thereby improving the high temperature resistance and durability of the coil enameled wire. Although the enameled wire prepared by this patent has excellent high temperature resistance, the honeycomb silica nanotubes added therein are inorganic nanoparticles, which may affect the adhesion between the paint film and the metal wire. When the electrical equipment is used for a long time, there is a risk of separation between the paint film and the metal wire, affecting the safety of the use of the electrical equipment. Summary of the invention

[0004] The purpose of the present invention is to provide a production process for high-temperature resistant ultra-fine enameled wires, which solves the following technical problems: (1) The adhesion between the polyimide paint on the surface of ordinary enameled wires and the metal conductors is general, and they are prone to hollowing, damage or even falling off during long-term use, causing current leakage in electrical equipment and posing safety hazards; (2) The high-temperature resistance of ordinary enameled wires is general, which makes it difficult to meet the long-term use requirements in high-temperature environments. They are prone to cracking and aging in high-temperature environments, which affects their service life.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A high temperature resistant ultra-fine enameled wire production process, characterized in that it includes the following production steps:

[0007] Step 1: Smelt the copper block, roll and stretch it, and wash it with deionized water to obtain a copper wire with a diameter of 55-65 μm;

[0008] Step 2: immerse the copper wire into the modified polyimide paint, fully coat it, bake it at 200-230°C for 12-15min, and coat the surface with polyurethane insulating paint and PA11 lubricant in turn after curing, and roll it up after drying to obtain the enameled wire;

[0009] The modified polyimide paint comprises the following raw materials in parts by weight: 5-8 parts of polycarbonate diamine, 60-80 parts of N,N-dimethylformamide, 6-10 parts of functional dianhydride, 8-10 parts of chain-extended bismaleimide solution with a solid content of 25-28%, 1-2 parts of boron nitride, 3-5 parts of isocyanate, and 50-80 parts of toluene.

[0010] Furthermore, the boron nitride particle size is 10-50 μm.

[0011] Furthermore, the preparation method of the polycarbonate diamine comprises the following steps:

[0012] S1: placing polycarbonate diol and dimethylvinyl chlorosilane in acetone, stirring and mixing them thoroughly, introducing nitrogen, heating and refluxing to react, and collecting the product after the reaction is completed to obtain terminal olefin polycarbonate;

[0013] S2: Place terminal olefin polycarbonate and 3-amino-5-mercapto-1,2,4-triazole in toluene, add photoinitiator, and heat at 1.8 mw / cm 2 The reaction was carried out under ultraviolet irradiation for 1.5-2h, and the product was collected after the reaction to obtain polycarbonate diamine.

[0014] In this scheme, the hydroxyl groups at both ends of the polycarbonate diol structure react with the silicon chlorine in the dimethylvinyl chlorosilane structure to obtain a terminal alkenyl polycarbonate with a silicon-oxygen bond. Then, under ultraviolet irradiation and the action of a photoinitiator, the alkenyl group in the terminal alkenyl polycarbonate structure undergoes a click reaction with the mercapto group in the 3-amino-5-mercapto-1,2,4-triazole structure to obtain a polycarbonate diamine. When this polycarbonate diamine is used as a component of a polyimide paint, the flexible chain segment of the polycarbonate diamine can improve the flexibility and reduce the risk of cracking while maintaining the heat resistance of the polyimide paint. The silicon-oxygen bond and the triazole ring structure in its structure can produce a synergistic effect in the polyimide paint and jointly enhance the high temperature resistance of the polyimide paint, so that the finally prepared enameled wire has excellent high temperature resistance, can meet the use requirements in a high temperature environment, is not easy to crack, has a good protective effect and insulation effect on the internal metal conductor, ensures the safety of the enameled wire, and effectively extends the service life of the enameled wire.

[0015] Furthermore, in step S1, the time of the temperature rising reflux reaction is 10-15h.

[0016] Furthermore, in step S2, the photoinitiator is any one of benzoin dimethyl ether and benzoin diethyl ether.

[0017] Furthermore, the preparation method of the functional dianhydride comprises the following steps:

[0018] SS1: Put polyethylene glycol diglycidyl ether and gallic acid in xylene, mix and stir thoroughly, add tetrabutylammonium bromide, heat to react, remove the solvent after reduced pressure distillation, and collect the product to obtain modified polyethylene glycol diglycidyl ether;

[0019] SS2: Place modified polyethylene glycol diglycidyl ether and bromomaleic anhydride in N,N-dimethylformamide, mix and stir thoroughly, add a catalyst, heat to 60-70°C and react for 5-8h, remove the solvent by rotary evaporation, and collect the product to obtain functional dianhydride.

[0020] In this scheme, under the action of tetrabutylammonium bromide, the epoxy groups at both ends of the polyethylene glycol diglycidyl ether structure react with the carboxyl groups in the gallic acid structure to obtain modified polyethylene glycol diglycidyl ether, and then under the action of a catalyst, the hydroxyl groups in the modified polyethylene glycol diglycidyl ether structure react with the active bromine in the bromomaleic anhydride structure to obtain a functional dianhydride. This functional dianhydride can participate in the preparation process of the polyimide paint. Its structure contains a pyrogallol structure and a large number of ether bonds, which can interact with the metal wire. The two produce a synergistic effect, significantly enhancing the adhesion between the polyimide paint and the metal wire, ensuring that the paint film is tightly attached to the surface of the copper wire, effectively preventing current leakage between the wires or between the wire and the external environment, ensuring the safety of electrical equipment, and when the prepared enameled wire is subjected to stress changes, the close combination of the polyimide paint and the metal wire makes it difficult for the paint film to produce hollowing, cracking or even falling off, significantly improving the safety and durability of the enameled wire.

[0021] Furthermore, in step SS1, the temperature of the temperature-raising reaction is 55-65° C., and the time is 5-6 hours.

[0022] Furthermore, the catalyst is any one of potassium carbonate, sodium carbonate and triethylamine.

[0023] Furthermore, the preparation method of the modified polyimide paint comprises the following steps:

[0024] The polycarbonate diamine and N,N-dimethylformamide are fully mixed and stirred, and functional dianhydride is added. After reacting for 5-6 hours, a chain-extending bismaleimide solution is added, and boron nitride is added. The mixture is stirred at a rate of 200-300 r / min for 15-20 minutes. Isocyanate is added and stirring is continued for 20-25 minutes. Toluene is added to adjust the solid content and viscosity to obtain a modified polyimide paint.

[0025] Beneficial effects of the present invention:

[0026] The present invention utilizes the prepared polycarbonate diamine and functional dianhydride to jointly prepare the modified polyimide paint, so that the modified polyimide paint has excellent adhesion and high temperature resistance. When the modified polyimide paint is used to prepare the enameled wire, the prepared enameled wire paint film has strong bonding ability with the metal wire, can effectively prevent the leakage of current, ensure the safety of the use of electrical equipment, can still work stably in a long-term high temperature environment, has good durability, and has a long service life.

[0027] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0029] Figure 1 The present invention is a flowchart of the enameled wire production process. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] Preparation of polycarbonate diamine

[0033] S1: 2.6 g of polycarbonate diol and 2.2 g of dimethylvinyl chlorosilane were placed in 80 ml of acetone, and after being fully stirred and mixed, nitrogen was introduced, and the temperature was raised to reflux for reaction for 10 hours. After the reaction was completed, the product was collected to obtain terminal olefin polycarbonate;

[0034] S2: 3.5 g of terminal olefin polycarbonate and 3 g of 3-amino-5-mercapto-1,2,4-triazole were placed in 100 ml of toluene, and 0.6 g of benzoin dimethyl ether was added. 2 The reaction was carried out under ultraviolet irradiation for 1.5 hours, and the product was collected after the reaction to obtain polycarbonate diamine.

[0035] The analysis of nitrogen and sulfur elements in terminal olefin polycarbonate and polycarbonate diamine using a Flash Smart elemental analyzer showed that terminal olefin polycarbonate contains neither nitrogen nor sulfur. The nitrogen content in polycarbonate diamine is 9.4%, and the sulfur content is 5.5%. The appearance of nitrogen and sulfur is due to the click reaction between the alkenyl group in the terminal olefin polycarbonate structure and the thiol group in the 3-amino-5-thiol-1,2,4-triazole structure.

[0036] Example 2

[0037] Preparation of functional dianhydrides

[0038] SS1: 2.8 g of polyethylene glycol diglycidyl ether and 2.6 g of gallic acid were placed in 60 ml of xylene, and after thorough mixing and stirring, 0.05 g of tetrabutylammonium bromide was added, and the temperature was raised to 55°C for reaction for 5 h. The solvent was removed by vacuum distillation, and the product was collected to obtain modified polyethylene glycol diglycidyl ether;

[0039] SS2: Place 3.6 g of modified polyethylene glycol diglycidyl ether and 3 g of bromomaleic anhydride in 100 ml of N,N-dimethylformamide, mix and stir thoroughly, add 0.02 g of potassium carbonate, heat to 60°C and react for 5 hours. After rotary evaporation to remove the solvent, collect the product to obtain functional dianhydride.

[0040] The content of maleic anhydride in modified polyethylene glycol diglycidyl ether and functional dianhydride was tested by titration. 1g of modified polyethylene glycol diglycidyl ether and functional dianhydride were weighed as samples, 80ml of toluene was added, and the mixture was heated under reflux for 1h and mixed thoroughly. An excess of 0.1mol / L KOH-ethanol standard solution was added, and the mixture was heated under reflux for 10h. After cooling, 1ml of phenolphthalein indicator was added, and a back titration operation was performed using 0.1mol / L HCl-isopropanol standard solution. The volumes of the consumed KOH-ethanol standard solution and the neutralized HCl-isopropanol standard solution were recorded, and the content of maleic anhydride in the sample was calculated according to the following formula: W=9.806(VC-V1C1) / 2m; Formula: Where: W is the mass fraction of maleic anhydride in the sample, %; C is KOH-ethanol standard solution, mol / L; C1 is HCl-isopropanol standard solution, mol / L; V is the volume of excess KOH-ethanol standard solution added, ml; V1 is the volume of HCl-isopropanol standard solution consumed by back titration neutralization alkali, ml; m is the mass of the sample, g; After calculation, the modified polyethylene glycol diglycidyl ether does not contain maleic anhydride, and the content of maleic anhydride in the functional dianhydride is 8.26%, because the hydroxyl group in the modified polyethylene glycol diglycidyl ether structure reacts with the active bromine in the bromomaleic anhydride structure, and the maleic anhydride group is introduced into the modified polyethylene glycol diglycidyl ether structure.

[0041] Example 3

[0042] Preparation of modified polyimide paint

[0043] 5 g of polycarbonate diamine and 60 ml of N, N-dimethylformamide were fully mixed and stirred, 6 g of functional dianhydride was added, and after reacting for 5 hours, 8 ml of extended chain bismaleimide solution with a solid content of 25% was added, 1 g of boron nitride powder was added, and stirred at a rate of 200 r / min for 15 min, 3 g of isocyanate was added, and stirring was continued for 20 min, and 50 ml of toluene was added to adjust the solid content to obtain a modified polyimide paint.

[0044] Example 4

[0045] Preparation of modified polyimide paint

[0046] 6.5 g of polycarbonate diamine and 70 ml of N, N-dimethylformamide were fully mixed and stirred, 8 g of functional dianhydride was added, and after reacting for 5.5 hours, 9 ml of extended chain bismaleimide solution with a solid content of 26% was added, 1.5 g of boron nitride powder was added, and stirred at a rate of 250 r / min for 17 min, 4 g of isocyanate was added, and stirring was continued for 23 min, and 65 ml of toluene was added to adjust the solid content to obtain a modified polyimide paint.

[0047] Example 5

[0048] Preparation of modified polyimide paint

[0049] 8 g of polycarbonate diamine and 80 ml of N, N-dimethylformamide were fully mixed and stirred, 10 g of functional dianhydride was added, and after reacting for 6 hours, 10 ml of extended chain bismaleimide solution with a solid content of 28% was added, 2 g of boron nitride powder was added, and stirred at a rate of 300 r / min for 20 min, 5 g of isocyanate was added, and stirring was continued for 25 min, and 8 ml of toluene was added to adjust the solid content to obtain a modified polyimide paint.

[0050] With reference to standard GB / T9286-2021, the modified polyimide paint in Example 3-Example 5 and the commercially available polyimide paint were used as samples for adhesion grade detection. The commercially available polyimide paint was purchased from Jining Tangyi Chemical Co., Ltd. The specific test results are shown in the following table:

[0051] Adhesion grade Example 3 Level 0 Example 4 Level 0 Example 5 Level 0 Commercially available polyimide paint Level 1

[0052] It can be seen from the above table that the adhesion level of commercially available polyimide paint needs to be improved. During long-term use, since the enameled wire may be subjected to mechanical stress such as bending and stretching, the paint film is difficult to adhere tightly to the surface of the copper wire, thereby posing a risk of current leakage between the wires, making it difficult to ensure the normal operation and safety of electrical equipment. The modified polyimide paint prepared in Examples 3 to 5 has an adhesion level of 0, has excellent adhesion ability, can effectively enhance the bonding force between the paint film and the copper wire, and makes the prepared enameled wire not easy to fall off when subjected to stress, thereby effectively improving the safety and durability of the enameled wire.

[0053] Example 6

[0054] Preparation of enameled wire

[0055] Step 1: Smelt the copper block, roll and stretch it, and wash it with deionized water to obtain a copper wire with a diameter of 55 μm;

[0056] Step 2: immerse the copper wire into the modified polyimide paint, fully coat it, bake it at 200°C for 12 minutes, and coat the surface with polyurethane insulating paint and PA11 lubricant in turn after curing. After drying, roll it up to obtain the enameled wire.

[0057] Example 7

[0058] Preparation of enameled wire

[0059] Step 1: Smelt the copper block, roll and stretch it, and wash it with deionized water to obtain a copper wire with a diameter of 60 μm;

[0060] Step 2: immerse the copper wire into the modified polyimide paint, fully coat it, bake it at 220°C for 13 minutes, and coat the surface with polyurethane insulating paint and PA11 lubricant in turn after curing. After drying, roll it up to obtain the enameled wire.

[0061] Example 8

[0062] Preparation of enameled wire

[0063] Step 1: Smelt the copper block, roll and stretch it, and wash it with deionized water to obtain a copper wire with a diameter of 65 μm;

[0064] Step 2: immerse the copper wire into the modified polyimide paint, fully coat it, bake it at 230°C for 15 minutes, and coat the surface with polyurethane insulating paint and PA11 lubricant in turn after curing. After drying, roll it up to obtain the enameled wire.

[0065] Comparative Example 1

[0066] Preparation of enameled wire

[0067] Step 1: Smelt the copper block, roll and stretch it, and wash it with deionized water to obtain a copper wire with a diameter of 60 μm;

[0068] Step 2: immerse the copper wire into commercially available polyimide varnish, fully coat it, bake it at 220°C for 13 minutes, and coat its surface with polyurethane insulating varnish and PA11 lubricant in turn after curing. After drying, roll it up to obtain enameled wire; the commercially available polyimide varnish was purchased from Jining Tangyi Chemical Co., Ltd.

[0069] Performance Testing

[0070] The enameled wires prepared in Examples 6 to 8 and Comparative Example 1 were used as samples, and a thermal shock test was performed on the samples with reference to the standard GB / T27749-2011 to determine the heat resistance level of the samples. The specific test results are shown in the table below:

[0071] Heat resistance grade Example 6 H Example 7 H Example 8 H Comparative Example 1 F

[0072] It can be seen from the above table that the heat resistance of the enameled wire prepared in Comparative Example 1 is not as good as that of the embodiment. The enameled wires prepared in Examples 6 to 8 have stronger heat resistance and can better meet the use requirements in high temperature environments. They are not easy to crack or break at high temperatures, are safer to use, and have a longer service life.

[0073] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0074] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A high temperature resistant ultra-fine enameled wire production process, characterized in that: The production process includes the following steps: Step 1: Smelt the copper block, roll and stretch it, and wash it with deionized water to obtain a copper wire with a diameter of 55-65 μm; Step 2: immerse the copper wire into the modified polyimide paint, fully coat it, bake it at 200-230°C for 12-15min, and coat the surface with polyurethane insulating paint and PA11 lubricant in turn after curing, and roll it up after drying to obtain the enameled wire; The modified polyimide paint is made of the following raw materials in parts by weight: 5-8 parts of polycarbonate diamine, 60-80 parts of N,N-dimethylformamide, 6-10 parts of functional dianhydride, 8-10 parts of chain-extended bismaleimide solution with a solid content of 25-28%, 1-2 parts of boron nitride, 3-5 parts of isocyanate, and 50-80 parts of toluene; The preparation method of the functional dianhydride comprises the following steps: SS1: 2.8 parts of polyethylene glycol diglycidyl ether and 2.6 parts of gallic acid are placed in xylene, and after sufficient mixing and stirring, 0.05 parts of tetrabutylammonium bromide are added, the temperature is raised to react, the solvent is removed after reduced pressure distillation, and the product is collected to obtain modified polyethylene glycol diglycidyl ether; SS2: 3.6 parts of modified polyethylene glycol diglycidyl ether and 3 parts of bromomaleic anhydride are placed in N,N-dimethylformamide, mixed and stirred thoroughly, and then 0.02 parts of catalyst are added. The temperature is raised to 60-70°C and reacted for 5-8 hours. After rotary evaporation to remove the solvent, the product is collected to obtain functional dianhydride.

2. A high temperature resistant ultra-fine enameled wire production process according to claim 1, characterized in that: The particle size of the boron nitride is 10-50 μm.

3. A high temperature resistant ultra-fine enameled wire production process according to claim 1, characterized in that: The preparation method of the polycarbonate diamine comprises the following steps: S1: placing polycarbonate diol and dimethylvinyl chlorosilane in acetone, stirring and mixing them thoroughly, introducing nitrogen, heating and refluxing to react, and collecting the product after the reaction is completed to obtain terminal olefin polycarbonate; S2: Place terminal olefin polycarbonate and 3-amino-5-mercapto-1,2,4-triazole in toluene, add photoinitiator, and heat at 1.8 mw / cm 2 The reaction was carried out under ultraviolet irradiation for 1.5-2h, and the product was collected after the reaction to obtain polycarbonate diamine.

4. A high temperature resistant ultra-fine enameled wire production process according to claim 3, characterized in that: In step S1, the temperature rising and reflux reaction time is 10-15h.

5. A high temperature resistant ultra-fine enameled wire production process according to claim 3, characterized in that: In step S2, the photoinitiator is any one of benzoin dimethyl ether and benzoin diethyl ether.

6. A high temperature resistant ultra-fine enameled wire production process according to claim 1, characterized in that: In step SS1, the temperature of the temperature-raising reaction is 55-65° C. and the time is 5-6 hours.

7. A high temperature resistant ultra-fine enameled wire production process according to claim 1, characterized in that: The catalyst is any one of potassium carbonate, sodium carbonate and triethylamine.

8. The high temperature resistant ultra-fine enameled wire production process according to claim 1, characterized in that: The preparation method of the modified polyimide paint comprises the following steps: The polycarbonate diamine and N,N-dimethylformamide are fully mixed and stirred, and functional dianhydride is added. After reacting for 5-6 hours, a chain-extending bismaleimide solution is added, and boron nitride is added. The mixture is stirred at a rate of 200-300 r / min for 15-20 minutes. Isocyanate is added and stirring is continued for 20-25 minutes. Toluene is added to adjust the solid content and viscosity to obtain a modified polyimide paint.

Citation Information

Patent Citations

  • A polyimide coil enameled wire for high-speed rail and its preparation method

    CN109135553B

  • Medical devices comprising a co-polymer of a polyamide and a polycarbonate diamine

    CN101702913A

  • Preparation method of polyimide insulating paint and enameled wire

    CN114773988A